Ephemeral parasitism on blooming diatoms in a temperate estuary - Guinder, Valeria Ana (2017)
Parasites of phytoplankton influence phytoplankton bloom dynamics and may severely affect the type of food available for higher trophic levels. The incidence of such infection diseases is expected to increase across ecosystems worldwide under scenarios of global change. Here we report a massive parasite infection on two dominant diatoms of the austral winter bloom ? Thalassiosira pacifica and Chaetoceros diadema ? recorded during an extreme precipitation event in the Bahía Blanca Estuary, Argentina. The infection was concomitant with a marked drop in water salinity and affected more than 40 % of host populations. While the parasite on C. didema was not identified, the parasite on T. pacifica was most likely Pirsonia sp., a nanoflagellate with high host specificity. After the intense rainy period and the parasitic infection, the phytoplankton biomass dropped (>80 %) and the community structure shifted to a dominance of smaller species i.e. Thalassiosira curviseriata, T. hibernalis and T. minima. We discuss the implications that these modifications might have in the food web dynamics and the potential relation between precipitation driven-modifications in water properties and parasitism emergence in coastal eutrophic environments.